2013
DOI: 10.1542/peds.2013-1150
|View full text |Cite
|
Sign up to set email alerts
|

International Reach of Tobacco Marketing Among Young Children

Abstract: WHAT'S KNOWN ON THIS SUBJECT: Prosmoking messages, delivered through marketing and the media, can reach very young children and influence attitudes and behaviors around smoking. WHAT THIS STUDY ADDS:Marketing of tobacco and cigarette brands has successfully reached young children in low-and middle-income countries. More effective measures are needed to restrict the reach of tobacco marketing. abstract BACKGROUND: Prosmoking messages, delivered through marketing and the media, can reach very young children and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
20
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 27 publications
1
20
0
2
Order By: Relevance
“…As the United States and wealthier developed nations increased their tobacco regulation efforts and public health campaigns, tobacco industry marketing increased in poorer countries, and there is concern about smoking prevalences in low-and middle-income countries [2,3]. Indeed, a recent study [4] found that 68% of 5-and 6-year-olds in Brazil, China, India, Nigeria, Pakistan, and Russia could identify the logo for at least one brand of cigarette. These findings suggest a substantial reach of tobacco marketing to children at quite young ages in low and middle-income countries.…”
mentioning
confidence: 99%
“…As the United States and wealthier developed nations increased their tobacco regulation efforts and public health campaigns, tobacco industry marketing increased in poorer countries, and there is concern about smoking prevalences in low-and middle-income countries [2,3]. Indeed, a recent study [4] found that 68% of 5-and 6-year-olds in Brazil, China, India, Nigeria, Pakistan, and Russia could identify the logo for at least one brand of cigarette. These findings suggest a substantial reach of tobacco marketing to children at quite young ages in low and middle-income countries.…”
mentioning
confidence: 99%
“…La influencia puede ocurrir en jóvenes con baja autoestima y dependientes de las opiniones de sus pares, con quienes comparten características, actitudes y comportamientos. [22][23][24] Si los amigos o los padres fuman, hay mayor riesgo de que los adolescentes empiecen a fumar y elijan amigos fumadores. 17 Adicionalmente, estudios previos muestran otros riesgos asociados como el consumo de alcohol, peleas o consumo de drogas ilegales, entre otros, 25 lo cual prueba la necesidad de incorporar estrategias de control del tabaco en los programas que el Estado implementa en temas de salud, seguridad y desarrollo de adolescentes.…”
Section: Artículounclassified
“…31,32 Pese a la prohibición de realizar actividades de marketing dirigidas a menores de edad, 33 en Bolivia no hay ninguna institución estatal o municipal que controle las actividades de marketing del tabaco, el cual es engañoso y en muchas ocasiones está dirigido a los más jóve-nes. 22,34,35 La prohibición de toda forma de publicidad, promoción y patrocinio es uno de los aspectos clave que debe ser abordado en programas de control del tabaco nacionales, puesto que su prohibición total reduce la susceptibilidad a fumar. 35 Las advertencias sanitarias introducidas en 2011 probaron ser considerablemente visibles entre los adolescentes.…”
Section: Artículounclassified
“…A 2013 study showed that the majority of young children in lowand middle-income countries could correctly identify cigarette brand logos, and nearly a third of children in India reported that they wanted to smoke when they grow up. 4,5 Most teenagers are aware of the hazards of smoking; however, few are worried about them. Moreover, most teenage smokers quickly become addicted to nicotine and experience high relapse rates and debilitating withdrawal symptoms when they attempt to break the habit.…”
Section: Introductionmentioning
confidence: 99%